INTEGRASI KEARIFAN LOKAL BALI DALAM PEMBELAJARAN IPA MASA KINI - WIDIARINI, PUTU; SUASTRA, I WAYAN; ARNYANA, IDA BAGUS PUTU (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
ABSTRACT Science learning based on local wisdom in Bali is very important to understand in the context of relevant and contextual education. Integrating local wisdom into learning will instill values of love for the homeland and good character in students and can also be used as a way to preserve local culture. This research is a literature study that aims to analyze and synthesize literature related to the integration of Balinese local wisdom in science learning. This type of research is qualitative research. There are 15 articles in accredited national journals related to the integration of Balinese local wisdom in science learning. All articles are analyzed by synthesizing the integration of Balinese local wisdom in learning materials so that they become learning resources for students. The integration of Balinese local wisdom in science learning can be translated into the form of sources or learning materials, learning media, and the development of learning models that are integrated into the syntax of the learning model. Some Balinese local wisdom that has been utilized in science learning are 1) the magedong-gedongan ceremony, 2) the Nyepi holiday, 3) the Ngaben ceremony, 4) the Tri Hita Karana philosophy, and 5) the subak system. These five examples of Balinese local wisdom are integrated into science learning materials so that learning becomes more contextual and increases knowledge related to local culture with the aim of preserving local culture and forming good character in students. ABSTRAK Pembelajaran IPA berbasis kearifan lokal di Bali sangat penting untuk dipahami dalam konteks pendidikan yang relevan dan kontekstual. Pengintegrasian kearifan lokal dalam pembelajaran akan dapat menanamkan nilai-nilai cinta tanah air dan karakter baik bagi peserta didik sekaligus dapat dijadikan sebagai salah satu cara melestarikan budaya lokal. Penelitian ini merupakan penelitian studi pustaka yang bertujuan untuk menganalisis dan mensintesis literatur-literatur terkait dengan integrasi kearifan lokal Bali dalam pembelajaran IPA. Jenis penelitian ini adalah penelitian kualitatif. Terdapat 15 artikel pada jurnal nasional terakreditasi yang berkaitan dengan integrasi kearifan lokal Bali dalam pembelajaran IPA. Semua artikel dianalisis dengan mensintesis pengintegrasian kearifan lokal Bali dalam materi pembelajaran sehingga menjadi sumber belajar bagi peserta didik. Integrasi kearifan lokal Bali dalam pembelajaran IPA dapat diterjemahkan dalam bentuk sumber atau bahan belajar, media pembelajaran, dan pengembangan model pembelajaran yang diintegrasikan pada sintaks model pembelajaran. Beberapa kearifan lokal Bali yang telah dimanfaatkan dalam pembelajaran IPA yaitu 1) upacara magedong-gedongan, 2) hari raya Nyepi, 3) upacara Ngaben, 4) filosofi Tri Hita Karana, dan 5) sistem subak. Kelima contoh kearifan lokal Bali ini diintegrasikan ke dalam materi pembelajaran IPA sehingga pembelajaran menjadi lebih kontekstual dan menambah pengetahuan terkait budaya lokal dengan tujuan dapat melestarikan budaya lokal dan membentuk karakter baik peserta didik.